The performance and pathway of indole degradation by ionizing radiation. (January 2022) - He, Hang; Wang, Shizong; Wang, Jianlong
Abstract: Indole is a typical recalcitrant aromatic nitrogen heterocyclic compound, which usually exists in coal chemical wastewater, and cannot be effectively removed by conventional wastewater treatment process. In this study, ionizing radiation was applied for the degradation of indole in aqueous solution. The effect of absorbed dose (1, 2, 3 and 5 kGy), initial concentration of indole (10, 20, 40 and 100 mg/L) and pH (3, 5, 7 and 9) on the degradation of indole was investigated. The results showed that the removal efficiency of indole was 99.2% at its initial concentration of 10 mg/L, absorbed dose of 2 kGy, and pH of 5. In addition, quenching experiments confirmed that three reactive species, including hydroxyl radical, hydrated electron and hydrogen radical, contributed to indole degradation. Five intermediate products were identified during indole degradation, including 3-methylindole, 3-methylinodle radicals, hydroxylation inodole, anilinoethanol and isatoic acid. The possible pathway of indole degradation was proposed. The acute toxicity and chronic toxicity of intermediate products of indole degradation were significantly reduced, except for 3-methylindole. In summary, ionizing radiation is alternative technology for the degradation of indole in coal chemical wastewater. Graphical abstract: Image 1 Highlights: Effect of dose, initial concentration and pH on indole degradation was examined. Inorganic anions had no obvious influence on indole degradation. Five intermediate products were identified by LC-MS during indole degradation. The possible pathway of indole degradation was tentatively proposed. Ionizing radiation was effective to degrade indole in coal chemical wastewater.